(3GdJMcje aj efGRYGJ GdeTQhYGJ GdebGeI HfXGe GdTQGcI Hjf GdbWGYjf GdYGe hGdNGU (B/ s - (3TgGH aGQhb YHO GdMi YRJs; (3eMehO SejQ GdTQbGhi s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2014)
(3jgOa ehVhY GdHMK Edi EdbGA GdVhA Ydi CgejI GdJMcje HGYJHGQg ef Cge GdhSGFd GdHOjdI ddJbGVj , dJShjI GdefGRYGJ Hjf GdCWQGa aj GdeYGedGJ GdJLGQjI YGeI , haj GdeTQhYGJ GdebGeI HCSdhH GdeTGQcI Hjf GdbWGYjf GdYGe hGdNGU aj eTQhYGJ GdHfjI GdCSGSjI NGUI(B. (3EP Cf Jdc GdeTQhYGJ JJejR HVNGeI GdJehjd hJYOO GdYdGbGJ GdJYGbOjI hJTGHcgG , eeG bO jDOj Edi fThA GdefGRYGJ Hjf CWQGagG, hGdJj bO JDKQ Ydi SjQ GdeTQhY , hgh eG jJfGai eY acQI GdeQab GdYGe hGdPj jLH Cf jSjQ HGfJXGe hGVWQGO (B. (3hdeG cGfJ GdOhd , hNGUI GdfGejI , JYLR Yf JhajQ cGaI GdNOeGJ GdeWdhHI dcaGdI eSJhi eYjTI efGSH dehGWfjgG , aEfgG JdLC Edi ETQGc GdbWGY GdNGU ef CLd JhajQ GdJehjd hGdJbfjI GddGReI dJTjjO Jdc GdeTQhYGJ hGdJj JDKQ HTcd eHGTQ Ydi SjQ GdMjGI GdjhejI ddehGWf , hGdJj JdJRe GdOhdI HJhajQ MO COfi ef GdNOeGJ GdJj jSJajO efgG ehGWfjgG , hdeG cGf CSdhH GdTQGcI eY GdbWGY GdNGU aj eTQhYGJ GdHfjI GdCSGSjI jMbb Jdc GdCgOGa , abO JHfJg GdYOjO ef GdOhd hef HjfgG eUQ HebJVi GdbGfhf Qbe (B67 (3dSfI (B2010 (3hGdoeSei (B" (3bGfhf JfXje eTGQcI GdbWGY GdNGU aj eTQhYGJ GdHfjI GdCSGSjI hGdNOeGJ hGdeQGab GdYGeI (B" s
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdJLGQi, (B2014s
(3jTJed Ydi EQLGYGJ HHdjhLQGajI(B: (3UaMI (B364-418s
(3GdfU HGdYQHjI hGdedNU HGddZI GdEfLdjRjI hGdYQHjI(B.s
Keywords: (3GdbGfhf GdJLGQjs; (3GdJMcje s; (3GdbWGYjf GdYGe hGdNGU s; (3fXGe GdTQGcI s; (3GdJMcje GdGdcJQhfjs; (3CfhGY GdJMcjes; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdJLGQjs